2017
DOI: 10.1039/c7nj02863f
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanoprism-based paper as a ratiometric sensor for extending biothiol detection in serum

Abstract: A paper-based method with selectivity and a wider linear range for the detection of l-Cys in serum using DTNB-modified Ag nanoprisms (AgP-DTNB).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…As shown in the inset of Figure S3 , the color changed with the additions of different interferents. It has been shown that most amino acids have no interfering effects on the analysis of Xan, but compounds in the thiol-containing group, e.g., L-Cysteine, L-Glutathione, and sodium thiosulfate, which have stronger affinity to AgP [ 30 ], slightly interfere in the analysis of Xan. Zare et al have reported that L-phenylalanine can act as a reducing agent to cap gold nanoparticles [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…As shown in the inset of Figure S3 , the color changed with the additions of different interferents. It has been shown that most amino acids have no interfering effects on the analysis of Xan, but compounds in the thiol-containing group, e.g., L-Cysteine, L-Glutathione, and sodium thiosulfate, which have stronger affinity to AgP [ 30 ], slightly interfere in the analysis of Xan. Zare et al have reported that L-phenylalanine can act as a reducing agent to cap gold nanoparticles [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Paper-based colorimetric techniques have gained much attention due to their low cost, portability and wide application in various areas such as industry, public health, food safety and environmental monitoring. [1][2][3][4][5] With the rapid growth of the population and the industrial revolution, the level of environmental pollution is increasing day by day. Despite substantial progress made by engineers, scientists and environmentalists to combat environmental pollution, more facile, low-cost, fielddeployable techniques are the need of the era.…”
Section: Introductionmentioning
confidence: 99%